2013
DOI: 10.1891/1061-3749.21.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Instrument to Measure Reasoning About Managing Asthma in Older School-Age Children and Adolescents

Abstract: Background and Purpose This article describes development and evaluation of a 4-scenario instrument designed to measure reasoning abilities for managing asthma symptoms. Methods Existing literature informed creation of a reasoning template and the reasoning scenarios. Think-aloud interviews appraised scenario functionality. Experts assessed content validity. Data from 2 groups of students with asthma aged 9–15 years (N = 132 and 307) were used to evaluate psychometric properties. Results The scenarios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Caregivers completed the General Health History Survey (Kintner, , 2009) and four additional instruments not reported here. Students completed the Knowledge of Asthma Survey (Kintner, ), the Reasoning about Asthma Scenarios (Kintner et al, ), and three additional instruments not reported here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Caregivers completed the General Health History Survey (Kintner, , 2009) and four additional instruments not reported here. Students completed the Knowledge of Asthma Survey (Kintner, ), the Reasoning about Asthma Scenarios (Kintner et al, ), and three additional instruments not reported here.…”
Section: Methodsmentioning
confidence: 99%
“…This four‐scenario information processing survey completed by students, titled “What I Would Do,” was used to measure reasoning abilities for managing asthma symptoms (Kintner et al, ). Students are directed to read each scenario and then respond to eight questions by circling the most appropriate response option(s).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reasoning about asthma symptom management was identified as an essential part of the process of coming to accept asthma as a chronic condition, 35 more information was needed to operationalize the concept. Findings of a second qualitative think‐aloud study were used to develop the Reasoning about Asthma Scenarios 50 . We later added the Asthma Control Test 52 as a valid measure of asthma control.…”
Section: Theory Evaluation and Augmentationmentioning
confidence: 99%